Fitting the Puzzle Pieces: the Bigger Picture of XCI. Issue 2 (February 2016) - Maduro, Cheryl; de Hoon, Bas; Gribnau, Joost
Abstract : X chromosome inactivation (XCI) is a mammalian-specific process initiated in all female cells, leading to one inactivated X chromosome. The robust nature of XCI, and the complex mechanisms involved in directing this process, makes XCI an important model system to study all aspects of gene regulation. XCI is divided into distinct phases: initiation, establishment, and maintenance of the inactive X (Xi). Recent studies shed important new light on the mechanisms directing all three phases of XCI. These findings include new regulatory pathways in XCI initiation, and the identification of a plethora of new factors involved in establishing and maintaining the Xi. In this review, we will highlight and discuss these new findings in the bigger picture of XCI. Trends: X chromosome inactivation (XCI) initiation is accompanied by movement of both X inactivation centers in close proximity towards each other in the nucleus. New data indicate that this X-pairing process is not required for XCI regulation. Xist RNA spreads to gene-dense regions before gene-poor regions. Spreading is instructed by the higher order chromatin structure, with genes in close spatial proximity to the Xist locus being silenced prior to genes located further away of Xist . Three different screens have identified novel Xist -interacting proteins. In all screens, SPEN was identified as an Xist -interacting protein, and functional studies indicate SPEN to be an important factor in Xi silencing. High-resolution microscopy reveals novel insights into the structural characteristics of the Barr body.